ANALISIS DAMPAK EKONOMI KEGIATAN WISATA YOUTH CAMP DI TAMAN HUTAN RAYA WAN ABDUL RACHMAN (TAHURA WAR) - Nur Shafika; Bustanul Arifin; Teguh Endaryanto (Lampung University, 2020)
The main purposes of this research is to find out the characteristic of visitors, local workforces and business owners, the factors that affect the frequency of tourist visits, and to analyze the economic impact caused by the Youth Camp tourism activities. The location for the research is intentionally chosen Youth Camp in Taman Hutan Raya Wan Abdul Rachman. Contributing toward this research consists of 40 visitors, 10 people of local workforce, and 15 business owners. The data for the research were generated in December 2018 to February 2019 and analyzed using methods of descriptive qualitative and descriptive quantitative. The research findings showed that the Youth Camp visitors’ages range between 17-35 years old, originally came from Lampung Province, and on their final year in SMA or equivalent. Majority of them are students employed with income above IDR2,000,000.00, single and no liabilities responsibilities. The frequency of visitors who came to visit was mostly influenced by the distance, age and well known of the tourism place. The value impact obtained from the value of Keynesian Income Multiplier is 5.33, value of Ratio Income Multiplier Type I is 2.70, and value of Ratio Income Multiplier Type II is 3.83. Key words: economic impact, Keynesian multiplier, Youth Camp